Annual Reviewer Acknowledgement - Srivastava, Hari Mohan (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2019)
The Editorial team of the journal would like to thank the reviewers for their work in refereeing manuscripts during 2019.